Effectiveness of Brief Strategic Family Therapy on Marital Conflicts and Interpersonal Forgiveness - Bustin, Somayeh; Mirzaei , Seyed Hossein; Ghasemi Motlagh , Mehdi (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The objective of this study was to evaluate the effectiveness of brief strategic family therapy on marital conflicts and interpersonal forgiveness. Methodology: This quasi-experimental study utilized a pre-test, post-test, and follow-up design with a control group. The sample consisted of eight families who sought counseling services at a psychology center in District 1 of Karaj in 2023. Families were randomly assigned to either the experimental group, receiving brief strategic family therapy, or the control group, receiving no intervention. Data were collected using the Forgiveness Questionnaire by Ehteshami Zadeh et al. (2009) and the Marital Conflict Questionnaire by Sanaei (2008). The intervention included eight weekly sessions of 90 minutes each. Descriptive statistics, univariate and multivariate covariance analyses were employed to analyze the data. Findings: Results indicated a significant reduction in marital conflicts and an increase in interpersonal forgiveness in the experimental group compared to the control group. Specifically, the mean score of marital conflicts in the experimental group decreased from 157.3 (SD = 14.7) in the pre-test to 102.2 (SD = 9.8) in the post-test, and further to 101.3 (SD = 9.7) in the follow-up stage. The mean score of interpersonal forgiveness increased from 76.9 (SD = 6.8) in the pre-test to 98.3 (SD = 9.6) in the post-test, and slightly decreased to 96.3 (SD = 8.6) in the follow-up stage. The multivariate covariance analysis confirmed the significant differences between the experimental and control groups (p < 0.05). Conclusion: Brief strategic family therapy significantly reduces marital conflicts and enhances interpersonal forgiveness among couples.